An Exploratory Analysis of EFL Learners’ Use of Modal Auxiliary Verbs in their Written Performance: The case of KRI Universities - Omed Faraj, Lana; Farooq Jawad, Hoshang (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
It has frequently been reported that the English modal verbs pose problems for EFL learners, including Kurdish learners, at both recognition and production levels. This problematic nature is attributed to a variety of factors, including the complexities of using modal verbs, their syntactic behavior and subtle meanings. The study’s goal is to determine whether Kurdish EFL university students struggle with the structure of modals or their meanings and whether they have a sufficient understanding of English modal auxiliaries while they write in English. The study has set for itself a number of research questions to answer all of which cover the uses of the following modal verbs: Can, Could, May, Might, Must, Should, be able to. To achieve the study’s objectives, two types of procedures were used: theoretical and practical. The theoretical procedure entails presenting a theoretical framework of the English modal verb, which includes definitions, classifications, features, modal verb uses, etc. The practical procedure, on the other hand, consisted of two procedures. The first entails selecting a sample of Kurdish EFL learners, developing a test, and administering it to the chosen sample after ensuring its validity and reliability. The test results were analyzed using appropriate statistical SPSS tools. The findings revealed that Kurdish EFL students have poor knowledge of the correct use and meaning of modal verbs in English. Also, the majority of Kurdish EFL university students failed to correctly distinguish between should/must auxiliaries and were unable to grasp the potential semantic difference between them because they used them interchangeably the majority of the time. The second practical procedure was an interview of six lecturers from three universities in Kurdistan Region of Iraq and the finding of the interview was that according to the instructors’ answers, KRI students’ ability to use modal verbs is limited and they can correctly use modal verbs in writing only poorly. They perform better with regard to the form and structure of the modal verbs.